Red/near-infrared chromenoquinoline dyes for LEDs and mitochondria labeling. (September 2022) - Niu, Peixin; Tian, Rumeng; Liu, Zengrong; Ran, Jie; Liu, Jiaojiao; Li, Yuhan; Ren, Xiaojie; Liu, Xingjiang; Wei, Liuhe
Abstract: In this work, we have designed and synthesized for the first time a series of red/near-infrared chromenoquinoline-based fluorescent dyes. These dyes show long wavelength emission (600–821 nm), large stokes shift and good photostability. It was shown that these newly developed dyes are capable of being used in LEDs, as well as in bioimaging of live cells and zebrafish. Importantly, the near-infrared chromenoquinoline dye can be used as targeting probe for mitochondria with good labeling properties. Highlights: Optical properties of new red/near-infrared fluorescent dyes. Highly stable NIR fluorescent dyes. Near-infrared fluorescent dyes targeting mitochondria.